THE INFLUENCE OF LIFESTYLE HEDONISM AND SOCIAL MEDIA ON THE CONSUMPTIVE BEHAVIOR OF GENERATION Z MUSLIMS IN SAMARINDA CITY WITH SHARIA ECONOMIC LITERACY AS AN INTERVENING VARIABLE - Putri Putri; Irma Irma; Arista Arista (Journal on Islamic Economics, Finance & Banking [Z-CONOMICS], 2026)
Everyone meets their needs in different ways, but consumptive behavior often appears when people prioritize wants over needs. Technology and globalization have changed lifestyles, especially for Generation Z, who are strongly influenced by social media. In Islamic economics, the rise of consumptive behavior among Muslim Gen Z is a concern because sharia principles promote balanced consumption. Hedonistic lifestyles, focused on short-term pleasure and excessive spending, often go against these values. At the same time, social media greatly shapes how young people think and act through digital ads and influencer promotions. This study aims to analyze the influence of Lifestyle Hedonism and Social Media on the Consumptive Behavior of Generation Z Muslims in Samarinda City, with Sharia Economic Literacy as a mediating variable. The method used is a quantitative approach with purposive sampling technique and Slovin formula, resulting in 100 respondents. Data analysis techniques in this study are Instrument Test, Classical Assumption Test, Multiple Linear Regression Test and Hypothesis Test using SPSS 25. Sharia Economic Literacy is tested because it helps explain how Lifestyle Hedonism and Social Media affect Consumptive Behavior, so their direct effects must also be analyzed. The results show that Lifestyle Hedonism and Social Media have a significant effect on Sharia Economic Literacy. Lifestyle Hedonism has a negative effect on Consumptive Behavior, while Social Media and Sharia Economic Literacy have a positive effect on Consumptive Behavior. Sharia Economic Literacy is proven to partially mediate the relationship between independent variables and Consumptive Behavior.